Assessing performance management in transnet - Moeletsane, Faith (My University, 2020)
State-Owned Enterprises (SOEs) are vital for the development of South Africa’s strategic sectors (Fourie, 2014). They have been a significant mechanism for driving economic growth and the reduction of poverty since 1994 (Kikeri,2018). They are critical in addressing market failure and for the growth of South Africa’s strategic sectors, “especially energy, transport, telecommunications and manufacturing” (Fourie, 2014, p.1). The PRC has undertaken extensive research and based on that provided recommendations that should be adopted across all SOEs in South Africa. The PRC notes the importance of ensuring effective performance management and monitoring of SOEs as critical, and important that SOEs carry through their mandate with effectiveness and efficiency due to the heavy reliance that the State has on the SOEs (PRC,2016. Through referencing large SOEs such as Eskom, SAA and Denel and their questionable performance over the last ten years that an opportunity to assess the impact of performance management in an SOE is imperative. In President Cyril Ramaphosa’s February 2019 State of the Nation Address (SONA) he makes mention of restoring stability in strategic entities as of the critical decisions taken (SONA, 2019). The president announced, “the establishment of the Presidential SOE Council, which will provide political oversight and strategic management in order to reform, reposition and revitalise SOEs, to ensure that SOEs play their mandated role as catalysts of economic growth and development” (SONA,2019). South Africa is not exempt from the global woes that face the public sector on the delivery on quality services to all its people; maximising of available resources, effective and fruitful public private partnerships, state safety and security, dealing with migration, employment, inequality and poverty, however there is a need to look at alternatives to Public Sector Management to 12 overcome these pressing challenges (Brinkerhoff & Brinkerhoff, 2015). Performance Management is thus important as it drives performance at both the strategic and individual level, encouraging improvement both on management and subordinates (Bussin, 2012). This study closely looks into the governance of SOEs by assessing the implementation of performance management. Field research will be conducted at Transnet one of the biggest SOEs in which the Department of Public Enterprises (DPE) “provides shareholder oversight” (Fourie, 2014, p. 5). The study contributes to the body of knowledge by outlining the practices, processes and applications of performance in the SOE and lessons that can be learnt.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Public and Development Management to the Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2020
Keywords: State-owned enterprises; Performance management; UCTD; Transnet; Key Performance Areas; SDG-8: Decent work and economic growth